Prevalence of Hepatitis C Virus Infection among People Attending a Voluntary Screening Centre in Masaka, Nasarawa State, Nigeria - GRI, Pennap; II, Nuhu; VB, Oti (The Asia Journal of Applied Microbiology, 2017)
Hepatitis C virus (HCV) is an emerging public health problem in Nigeria. This study therefore determined the seroprevalence of this virus among people of a rural settlement in Nigeria during which 600 people were screened for HCV infection. Five ml of blood was collected from each participant, the serum harvested and screened for anti- HCV using a Chromatographic rapid test kit (ACON Inc. USA) according to the manufacturer’s instructions .The overall prevalence of HCV infection in this population was 24.2% being higher among males (23.7%) than females (23.7%) (p 0.05). Only Educational level had a significant association with infection (p < 0.05). When stratified by age infection was highest among those aged 21 -30 years (27.4%) and least among those aged 51 years and above (3.6%) (p 0.05). Occupation and marital status also had no statistically significant relationship with viral infection. The 24.2% infection rate reported in this population is a cause for alarm because it means there is a high viral reservoir in the area. There is also a high number of persons likely to have end- stage liver diseases among these participants. The absence of identifiable risk factors is a major challenge to prevention and control and demonstrates the need for reevaluation of transmission routes in the locality. Screening should be available and affordable.